Predictive Validity of Evidence-Based Persuasion Principles: An Application of the Index Method - Armstrong, J. Scott (2016)
Purpose: To test whether a structured application of persuasion principles might help improve advertising decisions. Evidence-based principles are currently used to improve decisions in other complex situations, such as those faced in engineering and medicine. Approach: Scores were calculated from the ratings of 17 self-trained novices who rated 96 matched pairs of print advertisements for adherence to evidence-based persuasion principles. Predictions from traditional methods—10,809 unaided judgments from novices and 2,764 judgments from people with some expertise in advertising, and 288 copy-testing predictions from 5,285 judgments—provided benchmarks. Findings: The higher adherence to principles' consensus score correctly predicted the more effective ad for 75% of the pairs. Copy testing was correct for 59% and expert judgment was correct for 55%. Guessing would provide 50% accurate predictions. Combining judgmental predictions led to substantial improvements in accuracy. Research limitations: Ads for high-involvement utilitarian products were tested on the assumption that persuasion principles would be more effective for such products. The measure of effectiveness that was available—day-after-recall—is a proxy for persuasion or behavioral measures. Practical implications: Pretesting ads by assessing adherence to evidence-based persuasion principles in a structured way helps in deciding which ads would be best to run. Such a procedure also identifies how to make an ad more effective. Originality: This is the first study in marketing, and in advertising specifically, to test the predictive validity of evidence-based principles. In addition, the study provides the first test of the predictive validity of the index method for a marketing problem